An iridescent film of porous anodic aluminum oxide with alternatingly electrodeposited Cu and SiO2 nanoparticles - Chang, Menglei; Hu, Huawen; Quan, Haiyan; Wei, Hongyang; Xiong, Zhangyi; Lu, Jiacong; Luo, Pin; Liang, Yaoheng; Ou, Jianzhen; Chen, Dongchu (Beilstein Journal of Nanotechnology, 2019)
The structurally colored surface of anodic aluminum oxide (AAO) is highly useful for decoration and anti-counterfeiting applications, which are of significance for both scientific and industrial communities. This study presents the first demonstration of the fabrication of an iridescent film of porous AAO on an industrial aluminum alloy substrate, with alternatingly electrodeposited Cu and SiO2 nanoparticles (NPs). A rainbow effect was effectively obtained for the optimized sample with appropriate alternating electrodeposition times. The structure and optical properties of a series of the electrodeposited AAO-based thin film were investigated. The Cu and SiO2 NPs were found to be uniformly deposited into the porous structure of the AAO film, and the alternating electrodeposition repeating twice led to the formation of the optimal AAO-based thin film that exhibited a rainbow effect and superior anti-corrosion performance.
Keywords: aluminum alloys; anodic aluminum oxidation; interference-enabled color production; rainbow effect; structural color

(untitled) - Boinovich, L. B.; Modin, E. B.; Sayfutdinova, A. R.; Emelyanenko, K. A.; Vasiliev, A. L.; Emelyanenko, A. M. (ACS Nano, 2017)

(untitled) - Wei, H. L.; Elmer, J. W.; DebRoy, T. (Acta Mater., 2017)

(untitled) - Chen, K.; Scales, M.; Kyriakides, S. (Int. J. Mech. Sci., 2018)

(untitled) - Chang, M.; Wei, H.; Chen, D.; Hu, H.; Zhang, Y.; Ye, X.; Zeng, K.; Li, D. (Nano Res. Appl., 2017)

(untitled) - Wei, H.; Hu, H.; Chang, M.; Zhang, Y.; Chen, D.; Wang, M. (Ceram. Int., 2017)

(untitled) - Oddone, V.; Boerner, B.; Reich, S. (Sci. Technol. Adv. Mater., 2017)

(untitled) - Mrad, M.; Ben Amor, Y.; Dhouibi, L.; Montemor, M. F. (Surf. Coat. Technol., 2018)

(untitled) - Mugada, K. K.; Adepu, K. (J. Manuf. Processes, 2018)

(untitled) - Edalati, K.; Horita, Z.; Valiev, R. Z. (Sci. Rep., 2018)

(untitled) - Fu, J.; Wang, S.; Wang, K. (J. Mater. Sci., 2018)

(untitled) - Martinez, N.; Kumar, N.; Mishra, R. S.; Doherty, K. J. (J. Mater. Sci., 2018)

(untitled) - Mrad, M.; Dhouibi, L.; Montemor, M. F. (Prog. Org. Coat., 2018)

U.S. Patent - Seki, Y.; Ebihara, K. (Surface-treated aluminum material and zinc-supplemented aluminum alloy, 2017)

(untitled) - Gao, W.; Rigout, M.; Owens, H. (Appl. Surf. Sci., 2016)

(untitled) - Zhao, X.; Meng, G.; Xu, Q.; Han, F.; Huang, Q. (Adv. Mater. (Weinheim, Ger.), 2010)

(untitled) - Zhang, S.-Y.; Xu, Q.; Wang, Z.-J.; Hao, S.-Z.; Sun, C.-X.; Ma, W.-J. (Surf. Coat. Technol., 2018)

(untitled) - Liang, C.-J.; Huang, K.-Y.; Hung, L.-T.; Su, C.-Y. (Surf. Coat. Technol., 2017)

(untitled) - Wei, H.; Chen, D.; Hu, H.; Chang, M.; Ye, X.; Wang, M. (RSC Adv., 2017)

(untitled) - Tong, L.; Qi, W.; Wang, M.; Huang, R.; Su, R.; He, Z. (Small, 2016)

(untitled) - Kinoshita, S.; Yoshioka, S.; Miyazaki, J. (Rep. Prog. Phys., 2008)

(untitled) - Liu, Y.; Chang, Y.; Ling, Z.; Hu, X.; Li, Y. (Electrochem. Commun., 2011)

(untitled) - Shi, P.; Wang, F.; Zhu, J.; Zhang, B.; Zhao, T.; Wang, Y.; Qin, Y. (Ceram. Int., 2017)

Electronics, Electrical Engineering and Information Science - Yang, S. M.; Gu, J. J.; Qi, Y. K. (The study on structural color of porous anodic alumina thin film fabricated in phosphoric electrolyte, 2016)

(untitled) - Gao, W.; Rigout, M.; Owens, H. (J. Nanopart. Res., 2017)

(untitled) - Xu, Q.; Sun, H.-Y.; Yang, Y.-H.; Liu, L.-H.; Li, Z.-Y. (Appl. Surf. Sci., 2011)

(untitled) - Xu, Q.; Yang, Y.-H.; Liu, L.-H.; Gu, J.-J.; Liu, J.-J.; Li, Z.-Y.; Sun, H.-Y. (J. Electrochem. Soc., 2011)

(untitled) - Xu, Q.; Yang, Y.; Gu, J.; Li, Z.; Sun, H. (Mater. Lett., 2012)

(untitled) - Yavuz, G.; Zille, A.; Seventekin, N.; Souto, A. P. (Carbohydr. Polym., 2018)

(untitled) - Jia, Y.; Zhang, Y.; Zhou, Q.; Fan, Q.; Shao, J. (Thin Solid Films, 2014)

(untitled) - Jia, Y.; Zhang, Y.; Liu, G.; Zhuang, G.; Fan, Q.; Shao, J. (J. Coat. Technol. Res., 2015)

(untitled) - Jia, Y. R.; Shao, J. Z.; Fan, Q. G. (Adv. Mater. Res., 2012)

(untitled) - Zhang, Z.; Zhang, J.; Hou, X.; Wu, T.; Sun, H. (Thin Solid Films, 2014)

(untitled) - Yuan, W.; Zhou, N.; Shi, L.; Zhang, K.-Q. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Li, Q.; Zeng, Q.; Shi, L.; Zhang, X.; Zhang, K.-Q. (J. Mater. Chem. C, 2016)

(untitled) - Zeng, Q.; Ding, C.; Li, Q.; Yuan, W.; Peng, Y.; Hu, J.; Zhang, K.-Q. (RSC Adv., 2017)

(untitled) - Wang, Y.; Han, R.; Qi, L.; Liu, L.; Sun, H. (Appl. Opt., 2016)

(untitled) - Liu, H.; Sun, H.; Liu, L.; Hou, X.; Jia, X. (Opt. Mater., 2015)